162 Higher Mean Arterial Blood Pressures Following Spinal Cord Injury are Associated With Greater Neurological Recovery. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Hawryluk, Gregory W.J.; Whetstone, William; Saigal, Rajiv; Ferguson, Adam; Talbott, Jason; Bresnahan, Jacqueline; Pan, Jonathan; Beattie, Michael; Dhall, Sanjay S.; Manley, Geoffrey T.
Abstract: INTRODUCTION: Guidelines for the care of patients with acute spinal cord injuries (SCIs) recommend maintaining MAP values of 85 to 90 mm Hg for 7d following an acute SCI; however, little evidence supports this recommendation (1). We sought to better characterize the relationship between MAP values and neurological recovery. METHODS: Arterial line MAP values were collected every minute from 100 spinal cord injured patients over a 6-year period. Seventy-three patients also had American Spinal Injury Association Impairment Scale (AIS) grades determined on admission and at time of hospital discharge. The proportion of MAP values below thresholds were explored for values from 120 mm Hg to 40 mm Hg in 1 mm Hg increments; these thresholds were analyzed within 1 day, 3 days, 5 days, and 7 days of intensive care unit admission for a relationship with outcome. RESULTS: A total of 994, 875 q1 minute MAP values were recorded. Within 7 days of injury 28.2% of measures were below 85 mm Hg. Higher MAP values were consistently seen throughout the first 7d in patients achieving greater degrees of neurological recovery. A MAP threshold of 85 mm Hg robustly distinguished patients achieving a 1-point AIS grade improvement from those achieving 2 or 3 points of improvement. Patients achieving a 1-point AIS grade improvement had greater proportion of MAP recordings below 100 mm Hg than those who did not improve neurologically. CONCLUSION: This study provides strong evidence supporting a correlation between MAP values and neurological recovery but does not provide evidence of a causal relationship. It provides support for the notion of MAP thresholds in SCI recovery and the highest MAP values correlated with the greatest degree of neurological recovery. The results are concordant with current guidelines in suggesting that MAP thresholds >85 mm Hg may be appropriate following acute SCI.